The role of institutions in driving economic change: comparing the thoughts of Ibn Khaldūn and Douglass C. North - Khalid, Haniza (IIUM Press, 2015)
This article compares various elements of Ibn Khaldūn’s and Douglass C. North’s thoughts on the role of institutions in influencing or forcing economic change. There are a number of interesting similarities in ideas, thoughts, approaches, and methodologies, which prove that New Institutional Economics may actually mirror much of (and can benefit from) Ibn Khaldūn’s fourteenth century ideas than was previously thought. Both Ibn Khaldūn’s continuum of badāwah to ḥaḍārah and North’s theory on changes from informal to formal institutions lead to the same fundamental conclusions: (i) change is incremental as it is a result in small cumulative changes in the cost-benefit outcomes of the market agents over time, and therefore (ii) economic performance inevitably depends on the existence and effectiveness of formal institutions that alter those outcomes. It is also noted that ‘aṣabiyyah or group feeling, another cornerstone of Ibn Khaldūn’s thought, corresponds perfectly to North’s treatise that social cohesion and institutional efficiency are more important than the amount of resource endowment in bringing about economic development and change. In addition, Ibn Khaldūn’s views on the government’s commercial activities are reviewed in the study in light of North’s transaction costs and property rights framework.